Reflexões sobre o juízo de admissibilidade dos recursos excepcionais : delegabilidade e constitucionalidade - Souza, Maria Carolina Rosa de (2013)
The law of civil procedure should always be thought of under the premise of ensuring the jurisdicionado instruments able to deliver an effective adjudication, pervaded by legal certainty. In this context, the superior court system has been criticized about their procedures. Considering the purpose of the Supreme Court and the Superior Court of Justice and the importance of the extraordinary and special resources, it appears appropriate to examine its procedural aspects, especially in regard to the court split the admissibility of appeals. In this paper, present a reflection on the delegabilidade of the Court resorted to the completion of court admissibility of exceptional resources, especially from the perspective of the constitutional principle of the natural judge. Insofar as the pertinence of the admissibility of extraordinaries resources is the demonstration of public interest matter versed in it, it is imperative that only the Superior Court will do a judgment efetive admissibility in this regard. Considering this fact, it is proposed that the intake system will be overhauled, going to be held solely and definitively by the Superior Courts.